Professional knowledge of the family health strategy on sickle-cell disease - Laise Maria Formiga Moura Barroso; Telma Maria Evangelista Araújo; Brunna Eulálio Alves; Maria do Carmo de Carvalho e Martins (Universidade Federal do Estado do Rio de Janeiro, 2014)
Objective: To evaluate the knowledge of medical professionals and nurses of the family health strategy on sickle-cell disease. Method: This is a quantitative study of the universe of physicians and nurses that make up the family health strategy teams (n=104). The data were collected through a questionnaire in the period from March to May of 2012, descriptive and inferential analysis of the numeric variables. Results: The majority of the professionals were women (61.5%), specialized (85.6%) and having less than five years of experience in the family health strategy (34.6%). Part of the physicians (29.8%) have adequate knowledge on sickle cell anemia and 54.6% have regular knowledge on the disease, while more than half of nurses (54.4%) have inadequate knowledge. Conclusion: The findings point to the need for permanent education of the primary care professionals, since it is on the main port of access for users.